The Role of User Comments in Estimation of the Public Opinion Climate and Perceived Support for One's Opinion. (21st October 2019) - Soffer, Oren; Gordoni, Galit
Abstract: This article examines how user comments influence assessment of public opinion climate and perceived support for one's opinion. The effects of user-comment sentiment (positive vs. negative) and of user-comment content (with or without personal exemplification) were tested with an online experiment ( n = 1, 510). Results show that user-comment effects on estimates of public opinion depend mainly on the sentiment of the comments and not on their framing as opinions with or without personal exemplification. Negative comments significantly reduce readers' estimation of public opinion support of the issue dealt with by the article and affect the perceived support of one's opinion. Study results refer to the possible dangers in user comments deliberate manipulation in democratic public discussion.